Eruptive xanthomas secondary to severe hypertriglyceridemia - Wade Hopper; Spiro Veria; Logan Glosser; Anu Garg; Mohammed T Awad; Justin Smith; Shahab Ud Din (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Xanthomas are benign cutaneous manifestations of extracellular lipid accumulation. Eruptive xanthoma is characterized by the acute, widespread presentation of a papular rash and usually involves the back, buttocks, and extremities. Eruptive xanthoma is associated with hyperlipidemia, hypertriglyceridemia, and an increased long-term risk of atherosclerotic cardiovascular disease. We present a case of eruptive xanthoma accompanied by severe hypertriglyceridemia (10,164 mg/dL) in which the course of the disease was reversed following implementation of lipid-lowering pharmacotherapy.